2020
DOI: 10.1002/bio.3906
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 quantum dots as a specific fluorescence sensor for selection of rutin and for temperature sensing

Abstract: A selective and sensitive method for detecting rutin using MoS2 quantum dots (QDs) as a fluorescent probe is reported in the paper, a one‐step hydrothermal synthesis method was used to prepare MoS2 QDs. The synthesized MoS2 QDs had good stability and water solubility, and the fluorescence of MoS2 QDs was quenched by rutin due to the inner filter effect. There was a good linear relationship between the intensity of MoS2 QDs and rutin concentration ranging from 5.0 × 10−7 to 3.2 × 10−5 mol/L with a detection lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…53 The sensor, which operated at room temperature, showed excellent selectivity to sensing NO 2 gas in the presence of other interfering gases, an exceptionally low detection limit of 84 parts per billion, and the sensing properties did not vary found in fruits and grains which has been shown to have medicinal properties. 54,107 The authors found that on contact of rutin with the MoS 2 QDs, the fluorescence intensity decreased, and this decrease became more pronounced on addition of higher concentrations of rutin (Fig. 17).…”
Section: Sensing Applicationsmentioning
confidence: 96%
“…53 The sensor, which operated at room temperature, showed excellent selectivity to sensing NO 2 gas in the presence of other interfering gases, an exceptionally low detection limit of 84 parts per billion, and the sensing properties did not vary found in fruits and grains which has been shown to have medicinal properties. 54,107 The authors found that on contact of rutin with the MoS 2 QDs, the fluorescence intensity decreased, and this decrease became more pronounced on addition of higher concentrations of rutin (Fig. 17).…”
Section: Sensing Applicationsmentioning
confidence: 96%
“…28 The FT-IR peaks at 1640 cm −1 , 1412 cm −1 and 1120 cm −1 are assigned to the N-H bending vibration, and the stretching vibrations of -CN and C-O. [29][30][31] A weak peak at about 470 cm −1 is attributed to the vibration of Mo-S. 32 Compared with the FT-IR spectrum of I- MoS 2 QDs, a noticeable change is observed in the presence of Fe 3+ . In particular, there are obvious shis and intensity changes for the N-H bending vibration and the -CN stretching vibration peaks.…”
Section: Fluorescence Quenching Of I-mos 2 Qds By Fe 3+ Ionsmentioning
confidence: 99%
“…For instance, Sun et al fabricated molybdenum disulfide quantum dots through a one-step hydrothermal synthesis method for rutin detection with a linear range of 0.5–32 μM. 36 Sinduja and John synthesized fluorescent carbon dots using asparagine and used them for sensitive detection of rutin in the concentration range of 0.5–15 μM. 37 Lin et al constructed a dual-emission ratiometric fluorescence probe to selectively detect rutin by the electrostatic interaction of PVP-CuNCs and Rh6G, and the detection limit was 0.84 μM.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence analysis method has the advantages of convenient operation, low cost, and outstanding selectivity and sensitivity. Up to now, the fluorescence analysis method for rutin detection has also been reported. For instance, Sun et al fabricated molybdenum disulfide quantum dots through a one-step hydrothermal synthesis method for rutin detection with a linear range of 0.5–32 μM . Sinduja and John synthesized fluorescent carbon dots using asparagine and used them for sensitive detection of rutin in the concentration range of 0.5–15 μM .…”
Section: Introductionmentioning
confidence: 99%